HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT TINGGI SISWA PUTRA KELAS V SDN 018 TELUK KENIDAI KECAMATAN TAMBANG KABUPATEN KAMPAR - Abdul Muis; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s, the ability of the student’s high jump was not optimal yet. It is suspected because of explosive power leg muscles, and then failed because touch the crossbar. The purpose in this research is to see how much the corelations of explosive power leg muscle with the high jump result male student class V SDN 018 Teluk Kenidai Tambang District of Kampar . Population in this research is all male students calass V SDN 018 Teluk Kenidai amount 8 people. Based on population that is not so large and within the limits the researchers set the whole population used as a sample. The research sample as many as 8 people. Research instrument is measurement of explosive power leg muscles used vertical jump test and high jump test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : Shows that there is correlation explosive power leg muscles with the result of high jump, which shows rhitung (0,745)> rtabel (0,707)Key word : explosive power leg muscles, high jump.